Business, politics, and the state in Africa challenging the orthodoxies on growth and transformation - Kelsall, Tim. (London Zed Books, 2013)
Africa?s economies appear to have turned a corner; they no longer constitute the world?s slowest growing region. Commentators are beginning to ask whether a new generation of ?lions? is emerging to challenge the East Asian ?tigers?. This book goes behind the headlines to examine the conditions necessary not just for growth in Africa but for a wider business and economic transformation. Contrary to neoliberal economics, it argues that governments can play an important role in this and, controversially, that neo-patrimonial governance need not be an obstacle to improved economic conditions. Drawing on studies of Rwanda, Ethiopia, Tanzania and Ghana, this provocative book provides a radical new theory of the political and institutional conditions required for pro-poor growth in Africa.
Includes bibliographical references (p. [167]-184)
Keywords: Economic development-Africa.